A Fair Protection Model for Trademark Owners Unregistered Due to Registration Negligence - Muhammad Iridenta Tania; Gunardi Lie; Ade Adhari (jurnal.unprimdn.ac.id, 2026)
This study discusses a fair model of brand protection for unregistered brand owners due to registration negligence by examining the constitutive and declarative systems in Indonesia. The objective of the study is to formulate a legal protection model that grants rights based on actual use while guaranteeing legal certainty through formal registration. The method used is normative juridical with a qualitative approach, reviewing laws and regulations, court decisions, and related literature. The results show that a hybrid model combining the constitutive and declarative systems provides a balanced protection solution. Implementation of this model requires support from regulatory revisions, outreach to business actors, and effective law enforcement to prevent unfair competition. In conclusion, this hybrid protection model can improve fairness and certainty in brand protection in Indonesia.